DEVELOPMENT RESEARCH : STUDI KASUS PADA COMPUTER AIDED LEARNING (CAL) - Ely Susanti; Purwoko Purwoko; Zulkardi Zulkardi (Jurnal Pendidikan Matematika, 2008)
This study aims to (1) develop prototype software called computer aided learning (CAL) for Real Analysis courses, and (2) produce a valid and practice prototype software CAL in Real Analysis. CAL was tried out to prospective math teachers at the Department in Faculty of Teacher Training and Education of Sriwijaya University. That is used in this study is a developmental research that consists of analyzing, designing, evaluating, and revising. The Instruments for collecting data are questioner, observation, and test. Questioner is used to evaluate CAL. Observation is used to see the students’ skills and the students’ activities. Test is used to see students’ achievement after using CAL uses test. All data are analyzed using descriptive technique. The results of analysis are: (1) CAL Developing is just for sequences, series and limit function and the cycles are analyzing, designing, evaluating, and revising. (2) CAL prototype which is developed has been valid based on expert review and practice based on try out.